Impact of corporate culture on organizational effectiveness: research methodology and empirical assessments - Zhang xingang; Koshkina Olga (Scientific Research and Experimental Development, 2024)
In the context of globalization and rapidly changing market conditions, the effectiveness of organizations is becoming a key factor in their competitiveness. One of the important factors influencing organizational effectiveness is corporate culture. In modern research, the emphasis on corporate culture as a driver of success is increasingly confirmed, but requires a systematic and in-depth analysis. Companies that are able to develop a healthy and adaptive corporate culture have advantages in the field of innovation, employee motivation, and interaction with customers and partners. The purpose of this study is to study the relationship between corporate culture and organizational effectiveness based on empirical data. Both qualitative and quantitative methods were used to analyze the impact of corporate culture on organizational effectiveness. The novelty of the research lies in the integration of theoretical concepts of corporate culture with specific indicators of organizational effectiveness within the framework of one empirical study. In addition, the study offers a new approach to measuring corporate culture, including its impact on innovation, employee engagement and financial success of companies. Unlike traditional research, this study focuses on the dynamics of corporate culture and its ability to adapt to changes in the external environment.the results of the study showed that corporate culture has a significant impact on the key performance indicators of the organization. Companies with a strong, supportive and innovative culture show strong results in employee satisfaction, productivity and financial performance. At the same time, a culture focused on teamwork and development significantly increases the innovative potential and adaptability of the organization. The study also revealed that the flexibility of corporate culture and its ability to change in an unstable environment are important factors for long-term success.